The contribution of decentralised nursing education to social responsibility in rural Arctic Norway - Liss Trine Eriksen; Jeanette Elise Huemer (International Journal of Circumpolar Health, 2019)
This study explores and analyses decentralised nursing education in Finnmark County, Northern Norway, from 1991 to 2018. The study may have relevance for educational policy discussions and strategic planning. Our research question has been how decentralised nursing education can contribute to social responsibility by educating nurses rurally. The data collection includes documentation of 15 decentralised classes. The decentralised nursing education programme has been completed in nine rural communities in Finnmark County over 28 years and has resulted in 191 graduated nurses. Educating nurses locally influences recruitment and stability. The location of the study site determines where the recruited students come from. In future decentralised programmes, study sites should be located close to regions with a shortage of nurses. This is especially true of the eastern part of Finnmark, where recruitment to regular on-campus programmes is lowest. Limiting decentralised nursing programmes to local applicants should be considered. By prioritising local applicants, we will fulfil the university’s responsibility to place qualified nurses in all parts of Finnmark.